COVID-19 pandemic: ethical issues and recommendations for emergency triage - Wu, Leqian; Kong, Xiangjin (Frontiers in Public Health, 2023)
The current epidemic of Coronavirus Disease 2019 (COVID-19) has become a public health event worldwide. This paper discusses a series of ethical issues induced by the COVID-19 epidemic to emergency triage in hospitals, including the autonomy limitation of patients and waste of epidemic prevention resources due to over-triage, the safety problem of patients because of inaccurate feedback information from intelligent epidemic prevention technology, and conflicts between individual interests of patients and public interests due to the "strict" implementation of the pandemic prevention and control system. In addition, we also discuss the solution path and strategy of these ethical issues from the perspective of system design and implementation based on the Care Ethics theory.